Correlation of Inflammatory Markers and Disease Severity with Cardiovascular Autonomic Dysfunction in Indian Patients with Rheumatoid Arthritis - Mohan Babu Saminathan; Renuka Sharma; Arun Gogna; Anita Rani; Raj Kapoor (Indian Journal of Rheumatology)
Background: RA is an autoimmune disease characterized by chronic systemic inflammation, affecting approximately 1% of the population. Cardiovascular disease accounts for more than 40% of mortality in RA with cardiovascular autonomic nervous system dysfunction being commonly observed. Since few studies are available regarding the status of cardiac autonomic function in RA, we planned to study the same in RA patients and correlate it with their level of inflammatory markers and disease severity. Objectives: 1. To study the heart rate variability, inflammatory markers in RA and controls. 2. To assess the correlation of inflammatory markers and disease severity with HRV. Materials and Methods: The study was conducted on 35 diagnosed cases of RA and 35 controls. Short term heart rate variability was taken as an index of autonomic function. TNF-α and IL-10 were assessed in 3 ml overnight fasting serum. Severity of RA was assessed by DAS28 score. Result: Disease severity of RA was low. LF, NN50 and RANGE were significantly decreased in RA patients. TNF-α was significantly elevated in RA patients. Correlation of TNF-α with LF/HF ratio and DAS28 with RMSSD, NN50 and HF were found to be significantly positive. Conclusion: Our findings suggest that CAD is significantly correlated with inflammatory activity and disease severity in RA. Hence, we propose that HRV may serve as an accurate tool to screen RA patients for early signs of autonomic disturbance, which can greatly help to reduce future morbidity and mortality.